Physicochemical and Sensory Characteristics of Spreadable Liver Pâtés with Annatto Extract (Bixa orellana L.) and Date Palm Co-Products (Phoenix dactylifera L.) (2017)
ABSTRACT: Two novel ingredients were incorporated into spreadable liver pâtés to study their effect on physicochemical and sensory characteristics and their possible use in the meat industry. Fresh date (Phoenix dactylifera, cv. Confitera) co-products, as a paste (0%, 2.5% and 7.5%), and annatto (Bixa orellana) extract (0 and 128 mg/kg), as a colourant, and their combinations were incorporated into liver pâtés to study their effect on the final quality. The six formulations were analysed for chemical composition, physicochemical characteristics (pH, aw, colour, emulsion stability, and texture), and sensory properties. Pâtés tolerated suitable incorporation of date paste, providing emulsifying activity and being able to counteract to some extent the emulsion destabilisation caused by the annatto. All formulations showed an acceptable sensory quality, particularly pâtés with annatto and 7.5% date paste, which was softer, juicier, and presented redness values similar to the control as well as better emulsion stability. The combined use of these novel ingredients could be used as natural ingredients.